PENANAMAN KARAKTER TANGGUNG JAWAB MELALUI PEMBELAJARAN PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN PADA SISWA SMP ISLAM AL-FATTAHIYYAH TULUNGAGUNG - Mohamad David Ardiansyah; Bachrul Ulum (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2026)
The low level of students' responsibility character, indicated by late submission of assignments, minimal participation in learning activities, and non-compliance with school regulations, constitutes the main problem underlying this research. Pancasila and Civic Education (PPKn) is considered a strategic medium for internalizing the value of responsibility, as it encompasses moral, social, and civic dimensions that are directly relevant to students' daily lives. This research focuses on three aspects: the process of instilling responsibility character through PPKn learning, the role of teachers and school personnel, and the supporting and inhibiting factors involved in the process at SMP Islam Al-Fattahiyyah Tulungagung. This study employed a descriptive qualitative approach, with research subjects consisting of the school principal, the PPKn teacher, the guidance and counseling teacher, the head of student affairs, the homeroom teacher, and students of class VII E. Data were collected through non-participatory observation, semi-structured interviews, and documentation, then analyzed using the Miles and Huberman interactive model through the stages of data condensation, data display, and conclusion drawing, with validity tested through source and technique triangulation. The findings indicate that the instillation of responsibility character was carried out through contextual and participatory learning combined with disciplinary habituation practices such as classroom duty, punctual attendance, and timely task completion. The PPKn teacher served as facilitator, motivator, guide, and role model, supported by the synergy of all school members. Supporting factors included a conducive school environment and a religious culture rooted in the Islamic boarding school setting, while inhibiting factors comprised low awareness among some students and insufficient parental supervision at home. It is concluded that PPKn learning plays a significant role in shaping students' responsibility character in a sustained and continuous manner. ABSTRAK Penelitian ini dilatarbelakangi oleh rendahnya karakter tanggung jawab siswa yang tercermin dari perilaku seperti keterlambatan mengumpulkan tugas, kurangnya partisipasi dalam pembelajaran, serta ketidakpatuhan terhadap tata tertib sekolah. Pembelajaran Pendidikan Pancasila dan Kewarganegaraan (PPKn) dipandang sebagai sarana strategis dalam menginternalisasi nilai tanggung jawab karena memuat pendidikan moral, sosial, dan kebangsaan yang berkaitan langsung dengan kehidupan peserta didik. Penelitian ini bertujuan untuk mendeskripsikan proses penanaman karakter tanggung jawab melalui pembelajaran PPKn, menganalisis peran guru dan pihak sekolah, serta mengidentifikasi faktor pendukung dan penghambatnya di SMP Islam Al-Fattahiyyah Tulungagung. Penelitian menggunakan pendekatan deskriptif kualitatif dengan subjek penelitian meliputi kepala sekolah, guru PPKn, guru BK, waka kesiswaan, wali kelas, dan siswa kelas VII E. Pengumpulan data dilakukan melalui observasi, wawancara semi-terstruktur, dan dokumentasi, sedangkan analisis data menggunakan model interaktif Miles dan Huberman melalui tahapan kondensasi data, penyajian data, dan penarikan kesimpulan. Hasil penelitian menunjukkan bahwa penanaman karakter tanggung jawab dilakukan melalui pembelajaran kontekstual dan partisipatif, serta kegiatan pembiasaan seperti piket kelas, disiplin kehadiran, dan penyelesaian tugas tepat waktu. Guru PPKn berperan sebagai fasilitator, motivator, pembimbing, dan teladan, didukung oleh sinergi seluruh warga sekolah. Faktor pendukung meliputi lingkungan sekolah yang kondusif, budaya religius, dan kerja sama antar guru, sedangkan faktor penghambat berupa rendahnya kesadaran sebagian siswa dan kurangnya pengawasan orang tua. Pembelajaran PPKn terbukti berperan penting dalam membentuk karakter tanggung jawab siswa secara berkelanjutan.